Keratosis follicularis spinulosa decalvans: confirmation of linkage to Xp22.13-p22.2. Issue 4 (April 1998) - Porteous, M E; Strain, L; Logie, L J; Herd, R M; Benton, E C
Abstract : Keratosis follicularis spinulosa decalvans (KFSD) is a rare, X linked disorder with skin and eye involvement (MIM 308800). We have studied a large British family with KFSD using polymorphic markers from Xp21-p23 and obtained a lod score of 2.056 at theta=0 with markers proximal and distal to the KFSD candidate region Xp22.13-p22.2 identified by Oosterwijk et al. Our data confirm the linkage to Xp22.13-p22.2 observed in the previously reported Dutch family, but fail to narrow the candidate interval for the KFSD locus.